Validation of theory-based integrated modeling and new insights for a high-performance steady-state scenario with only RF heating on EAST. (1st July 2022) - Zhai, X.M.; Chen, J.L.; Xiang, N.; Gong, X.Z.; Huang, J.; Qian, J.P.; Xu, G.S.; Li, M.H.; Liu, H.Q.; Zang, Q.; Zhang, T.; Li, G.S.; et al.
Abstract: Theory-based integrated modeling is validated against high-performance steady-state core plasmas on EAST in the high poloidal beta ( β p ) regime with only RF heating. Reasonably good agreement between the modeling results and experimental measurements is obtained not only for the temperature profiles but also for the 11-chord line-integrated densities and Faraday angles for the first time. This validation effort demonstrates that the safety factor profiles can be non-reversed in high β p experiments on EAST. The inaccessibility for LH waves observed in conventional ray-tracing simulations for some high β p experiments is effectively mitigated by including the modeling of wave propagation in the scrape-off layer. The observed confinement improvement with density increasing (Gong et al 2019 Nucl. Fusion 59 086030) can be attributed to the reduction of turbulent transport by the collisional stabilization in trapped electron modes, rather than by the Shafranov shift stabilization effect which was proposed to be the major cause of confinement enhancement in previous literature. Based on the successful validation and newly gained physical insights, predictive modeling is performed for core plasma considering the future upgrade capacity of LH wave system and shows that the high-performance steady-state H-mode scenario on EAST can be extended to the regime with q 95 to be ITER relevant.